Loneliness, social isolation, and their discordance among older adults - Ward, Mark; Kenny, Rose; Layte, Richard (TILDA, 2019)
We have shown here that loneliness and social isolation are not a necessary fact of the ageing process and recent efforts to alleviate these potentially damaging phenomena should be encouraged. This is particularly important in light of the growing body of evidence that loneliness is damaging to quality of life and wellbeing among older adults. Importantly, we have also demonstrated a method by which both emotional loneliness and social isolation can be considered in conjunction with each other so that we can account for discrepancies between the two concepts. These discrepancies are important as they suggest that a one-size-fits-all approach to local or national policy interventions may not work. Instead, there is a need to address both the subjective and objective features of loneliness in order to positively impact the wellbeing of older adults. This research also highlights the need for healthcare professionals to consider loneliness during clinical assessments of their patients. Clinical interventions may also benefit from the application of social prescribing, whereby clinical staff refer their patients to non-clinical community groups and services. This provides a practical example of how the social, as well as physical, needs of older adults may be met. Finally, in order for researchers to support these efforts, it is critically important that attempts to better understand the mechanisms linking loneliness and poor outcomes are encouraged and adequately supported.
PUBLISHED
Keywords: Ageing; Irish Longitudinal Study on Ageing; Wellbeing; Loneliness; Social isolation; Ageing; Health; Relationships; Social exclusion; Social participation